A Cross-Platform Multifunctional Testbed for Vulnerability Attack - Yin Xinchun; Shen Xiaobin; Yuan Fuchao; Mao Bing; Xie Li (Proceedings : 2009 International Forum on Computer Science-Technology and Applications ; IFCSTA 2009 ; 25-27 December 2009, Chongqing, China / [edited by Zhou Qihai ; sponsored by IITAA, 2009)
Recently, the research on the detection and defense of malicious attacks are becoming the main subject of information security. Various tools and technologies of detecting and defense malicious attacks are proposed in an endless stream, tools detecting vulnerabilities as well. However, there is a lack of method to test and evaluate the correctness and validity of these technologies and tools. In this paper, we first analyzed the characteristics and disadvantages of existing tools and testbeds for vulnerability attack, and discussed popular software bug types, including buffer overflows and integer overflows. On that basis, proposed an enhanced testbed for vulnerability attack. Then introduced the components of the testbed and their design and implementation details. Finally, validated its correctness and availability by experiment.